KUALITAS PELAYANAN ROOM SERVICE HOTEL SWISS BELINN PEKANBARU - Kurniawan, Igo Adam; Sulistyani, Andri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Hotels include business presses on sales of services. Marketing services in general the same way of marketing products where the sales process aims to achieve the target set. One of the activities undertaken by the company to achieve sales goals is to implement good and efficient service to consumers. Without this kind of service efforts to increase sales volume is very difficult because of the many and tight competition that occurs today. Many Hotels provide facilities and services that are basically to attract guests / consumers. This study aims to find out how the quality of service Swiss hotel Belinn Pekanbaru. This research uses quantitative descriptive method to examine the problem in the lift by analyzing the guest response about the service Room service Swiss Belinn Pekanbaru hotel. The questionnaires were distributed as many as 100 people. While data collection techniques in this study using observation, interviews, questionnaires, and documentation. The results showed that respondents assessed the quality of service Room Service Swiss Hotel Belinn Pekanbaru is good. It is proven through the results of the average total gain of each of the overall variables (reliability, assurance, empathy, tangible, responsiveness). Thus the quality of Room Service service given Swiss hotel belinn pekanbaru can be maintained or can be improved again. Keywords: Quality, Service